Data Governance 101: IR's Critical Role in Data Governance. Issue 185 (2nd February 2021) - Hubbard, Dan; Freda, Augie; Swanagan, Andrea
Abstract: Building a culture of data governance at a higher education institution involves collaboration across the entire institution. Before the creation of formalized roles to perform data management and data governance functions at colleges and universities, these functions were performed by traditional institutional research personnel. Documentation and management of data for analysis have, for a long time, been part of the institutional researcher's forte. However, a concentrated effort in data management and governance is necessary to transform traditional reporting into a dynamic analytic landscape complete with adequate definitions and documentation, and often this goes beyond the scope of today's institutional research offices. The following article offers a framework for developing a data governance program in a higher education setting and highlights the critical role that institutional research offices can play in helping to build institutional capacity for a well‐documented and managed data landscape. Support and rationale for developing a program at your institution are offered, and helpful tips and pitfalls to avoid are provided.